Unravelling the high-altitude Nansen blue ice field meteorite trap (East Antarctica) and implications for regional palaeo-conditions. (1st March 2019) - Zekollari, Harry; Goderis, Steven; Debaille, Vinciane; van Ginneken, Matthias; Gattacceca, Jérôme; Timothy Jull, A.J.; Lenaerts, Jan T.M.; Yamaguchi, Akira; Huybrechts, Philippe; Claeys, Philippe
Abstract: Antarctic blue ice zones, the most productive locations for meteorite recovery on Earth, contain old ice that is easily accessible and available in large quantities. However, the mechanisms behind these meteorite traps remain a topic of ongoing debate. Here, we propose an interdisciplinary approach to improve our understanding of a meteorite trap in Dronning Maud Land (East Antarctica) on the Nansen blue ice field meteorite trap (2600–3100 m above sea level), where more than half of the Asuka meteorites have been collected. Based on 185 surface blue ice samples, one of the largest observed spatial patterns in oxygen isotopic variation to date is found. Relying on meteorites for which the terrestrial ages are determined using 14 C and 36 Cl, this surface ice is interpreted to date from the Last Interglacial up to the present-day. By combining state-of-the-art satellite derived surface velocities, surface mass balance modelling and ice flow modelling, we estimate that about 75–85% of the meteorites found on the ice field were supplied by ice flow after entering the ice sheet in an accumulation area of a few hundred square kilometres located south (upstream) of the ice field. Less than 0.4 new meteorites per year are supplied to the ice field through ice flow, suggesting that the hundreds of meteorites found 25 years after the first visit to this ice field mostly represent meteorites that were previously not found, rather than newly supplied meteorites. By combining these findings, the infall rate of meteorites from space is estimated, which is in line with values from the literature, but situated at the higher end of the range. A comparison of the oxygen isotopic variation of the surface blue ice to that of the European Project for Ice Coring in Antarctica (EPICA), Dronning Maud Land (EDML) ice core (located 750 km to the west, at the same elevation), suggests that the regional changes in topography have been relatively limited since the Last Interglacial, supporting theories of an overall stable East Antarctic Ice Sheet (EAIS) over this time period.